The Iraqi insurgency: Actors, strategies, and structures - Guido Steinberg (Stiftung Wissenschaft und Politik (SWP), 2006)
The Sunni insurgency in Iraq has entered its fourth year after the overthrow of Saddam Hussein and continues unabated. Today, Iraq is a failed state that will remain instable for years to come, and the Sunni insurgents can claim a large part of the responsibility. They will remain an important factor in Iraqi politics. Furthermore, since 2005 indications have multiplied that Jihadist organizations like al-Qaida in Iraq succeed in triggering a civil war by targeting the Shiite majority in the country. Therefore, the insurgency is developing into a conflict between Sunni rebels and Shiite militias; more and more civilians of both confessions are the victims.Germany and Europe have to prepare for continuing instability and possibly a civil war in Iraq. This could lead to turmoil in neighbouring countries, first and foremost Syria. On their part, Iran and Turkey might be tempted to intervene more directly than they already do. As European influence in Iraq is negligible, Germany and the EU should focus on the neighbouring countries. The foreign and interior ministers of Iran, Turkey, Syria, Jordan, Saudi Arabia, Kuwait and Egypt have met frequently since 2003 in order to discuss the regional implications of the events in Iraq. Germany and the EU should aim at fostering such initiatives with the long-term goal of establishing a (sub-)regional security architecture. (SWP-Research Papers / SWP)
Keywords: 320